(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2021)
Coffee is a popular beverage that is consumed worldwide. Flavor is an important aspect of excellent coffee. Fermentation was applied in the wash coffee processing to degrade the mucilage layer and to improve the flavor quality. Fermentation in non-washed gayo arabica coffee processing has not been widely reported. This study aims to analyze the effect of anaerobic fermentation on non-washed Gayo arabica coffee processing to obtain coffee with the highest sensorial score. Coffee fruit were processed and fermented for 0-48 hours. Sensorial score, volatile, and non-volatil compounds were observed at roasted bean. A significant increase in sensory test scores was obtained in the Pulped Natural (PN) process which was fermented with a score of 85.58 Â± 1.01. Concentrations of citric, malic, succinic, lactic, and acetic acids are varied between the treatments. Volatile analysis using SPME-GCMS produced 20 compounds with an Odor Active Value OAV> 1 consisting of aldehydes, furans, ketones, phenols, pyrazines, and terpenes. Î²-Damascenone was a compound that has the highest OAV values with honey-like, fruity, apple, and rose aroma characteristics that dominate PN and Black Honey (BH). Fermentation for 48 h in the PN process is suitable for use in Gayo with humid conditions and high altitudes.